Load Flow Study of Isolated Hybrid Microgrid for Village Electrification - Singh, Kuldip; M. Narendra Kumar, Dr; Satyasis Mishra, Dr (International Journal of Engineering and Technology, 2018)
The government has main concerns to provide the electricity 24/7 for each household in village across the country by 2020. To fulfill the demand for village electrification renewable energy sources are major focus. The isolated hybrid microgrid is playing the vital role for village electrification solution in India. The major sources for isolated hybrid microgrid are solar, bio-mass and wind energy for village electrification. In isolated microgrid, major challenges are reliability of system to fulfill the electricity demand in village 24/7 from renewable energy sources. In this work, a technical study carried out for load flow study of isolated PV hybrid microgrid for unbalance local distribution network in village. The study carried out by simulation approach with NR iterative method to analyze the unbalance load demand, load flow study, voltage profile, angle, THD% and power factor of isolated hybrid microgrid.Â Â